“LIKE” SELECTIVE VIOLENCE: Analysis of gang discourse through readers’ comments on Facebook of salvadorans digital newspapers - Carballo, Willian (Abierta. Anuario de investigación, 2015)
Social networks have made it easier for citizens with access to new technologies to express themselves and confront their political leaders. This topic, in El Salvador, points to the violence generated by gangs. This text analyzes the discourse of citizens on this problem. It is a discourse that shows the desire of the majority of Internet users to end violence through more violence, which they justify and even rejoice in, as long as the one who suffers it is the marero. A narrative that is also consistent with the journalistic accounts, which have incited fear, encouraged military repression as a solution and established the gangs as the only enemy of society. ECMH ABIERTA_II_N9- 2015-15-29.